2020
DOI: 10.1016/j.cortex.2019.11.005
|View full text |Cite
|
Sign up to set email alerts
|

How alliteration enhances conceptual–attentional interactions in reading

Abstract: In linguistics, the relationship between phonological word form and meaning is mostly considered arbitrary. Why, then, do literary authors traditionally craft sound relationships between words? We set out to characterise how dynamic interactions between word form and meaning may account for this literary practice. Here, we show that alliteration influences both meaning integration and attentional engagement during reading. We presented participants with adjective-noun phrases, having manipulated semantic relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 36 publications
(48 reference statements)
2
28
0
Order By: Relevance
“…The slowing down of reading upon encountering foregrounded language further predicted increased appreciation of the literary works, confirming Mukařovský's theory that the disruption of rapid default processing and increased awareness of stylistic features contributes to aesthetic appreciation (Van den Hoven et al, 2016). Neuroimaging evidence showed that foregrounding devices such as alliteration directly modulate attention and semantic integration (Egan et al, 2020). Evidence from neuroimaging research also shows that certain types of literary language (metaphors, idioms, and irony/sarcasm) increase activation in the parietal attention network (Bohrn et al, 2012), presumably by increasing processing demands.…”
Section: Introductionsupporting
confidence: 52%
“…The slowing down of reading upon encountering foregrounded language further predicted increased appreciation of the literary works, confirming Mukařovský's theory that the disruption of rapid default processing and increased awareness of stylistic features contributes to aesthetic appreciation (Van den Hoven et al, 2016). Neuroimaging evidence showed that foregrounding devices such as alliteration directly modulate attention and semantic integration (Egan et al, 2020). Evidence from neuroimaging research also shows that certain types of literary language (metaphors, idioms, and irony/sarcasm) increase activation in the parietal attention network (Bohrn et al, 2012), presumably by increasing processing demands.…”
Section: Introductionsupporting
confidence: 52%
“…The assumption that artistic composition can be measured is most obvious for poetry, with its interplay of meaning and form as manifested in rhythm and rhyme, and other aspects of poetic form, e.g., alliteration (cf. for instance Jakobson, 1960;Leech, 1969;Jacobs, 2015;Jacobs et al, 2016;Vaughan-Evans et al, 2016;König and Pfister, 2017;Menninghaus et al, 2017;Egan et al, 2020;Menninghaus and Wallot, 2021). Relevant studies of prose have mostly used summary statistics of properties extracted from text.…”
Section: Introductionmentioning
confidence: 99%
“…The slowing down of reading upon encountering foregrounded language further predicted increased appreciation of the literary works, confirming Mukařovský’s theory that the disruption of rapid default processing and increased awareness of stylistic features contributes to aesthetic appreciation 15 . Neuroimaging evidence suggested that foregrounding devices such as alliteration modulate attention and semantic integration 29 . Evidence from neuroimaging research also showed that certain types of literary language (metaphors, idioms, and irony/sarcasm) increase activation in the parietal attention network 30 , presumably by increasing processing demands.…”
Section: Introductionmentioning
confidence: 99%